Belt Conveyor Otomatis Sebagai Penyortir Kualitas Jagung Manis Berbasis Nodemcu Esp8266 - Ansyah Dani Fernando; Meriani Meriani; Mekar Ria Pangaribuan (UNIVERSITAS PROF. DR. HAZAIRIN, SH BENGKULU, 2023)
Conveyor belts that are controlled by a controller and programmed by a PC, are widely used in industry, ranging from quality control, sorting, security, carrying objects and many others. This conveyor belt uses a load sensor and a TCS3200 tcs load sensor. The process of getting quality corn with the two sensors will make it easier to sort the sorter